Illuminating Maya Foodways and Ethnoecology: Paleoethnobotanical Study of Classic Period Maya Agriculture and Environment at Budsilha - Pugliese, Melanie (My University, 2023)
A much debated and sensationalized aspect of Classic period Maya history pertains to the understanding of the intersections between foodways, agriculture and collapse. Traditional collapse models focusing on large city centers follow the framework of environmental degradation as a result of swidden agriculture and maize monocropping leading to the Classic period Maya collapse. New research utilizing paleoethnobotanical methodologies has begun to create the foundation for a new understanding of collapse. During the Classic period an amalgamation of agricultural methods including agroforestry, homegardens and milpas coupled with a broad range of food crop species such as manioc, arrowroot, sweet potato, lerén, and canna enabled resiliency of Classic period Maya communities. In the Usumacinta River region within the southern Maya lowlands, Budsilha, a smaller secondary political center of Piedras Negras, provides the ideal location to study Classic period subsistence strategies and plant use. The purpose of this study was to determine which plants were consumed and present in the environment during the Classic period and the role of maize in subsistence relative to wild taxa and root crops. Microbotanical analysis of phytoliths and starch grains recovered from artifact residues, human teeth, and sediments provided evidence of diverse subsistence and agricultural practices. Maya people inhabiting Budsilha during the Classic period grew various drought-resistant crops such as manioc, alongside expected crops like maize. These findings have implications for understanding Classic period Maya foodways, plant use, and the framing of Maya societal “collapse”. Understanding how Maya communities were able to sustain large populations during climatic shifts can provide possible solutions for countries undergoing similar stresses today.
Keywords: Archaeology; Paleoethnobotany; Mesoamerica; Plants; Maya; Foodways; Agriculture